Across-arc geochemical variation in the Jurassic magmatic zone, Southern Tibet: Implication for continental arc-related porphyry CuAu mineralization - Wang, R.; Tafti, R.; Hou, Z.; Shen, Z.; Guo, N.; Evans, Noreen; Jeon, H.; Li, Q.; Li, W. (Elsevier Science BV, 2017)
The Jurassic Gangdese arc hosts the giant Xietongmen (Xiongcun) porphyry CuAu magmatic-hydrothermal centre. In order to understand the tectonomagmatic framework of the arc and its controls on the origin and temporal-spatial distribution of porphyry mineralization we conducted extensive major and trace, and isotopic analysis on a suite of samples collected regionally. Geochemical variations were observed across the Jurassic arc from south to north, controlled by northward subduction of the Neo-Tethyan oceanic plate and overlying Lhasa lithosphere. In the frontal arc (latitude 29°-29.55°N), the magmas had high Ba/La and Ba/Th ratios, high eNd(t) (+3 to +7) values, and their zircons have high eHf(t) (+10 to +18) values, and heterogeneous O isotopic compositions (d18O=+3.6 to +6.6‰). The low titanium-in-zircon temperature and zircon saturation temperature (both average=~700°C) suggest that a greater flux of dehydration fluids from the subducting slab triggered partial melting of the mantle wedge in the southern arc. High zircon Eu/Eu* and Ce/Nd ratios (>0.4 and >20, respectively) indicate highly oxidized, fertile magmas, from which the Xietongmen porphyry CuAu deposit formed. In contrast, the interior arc (north of latitude 29.55°), close to the ancient Tibetan basement, shows low Ba/La and Ba/Th ratios, low eNd(t) (-0.1 to +2.5) and zircon eHf(t) (+2 to +12) values, and less heterogeneous zircon O isotopic compositions with higher d18O values. Higher titanium-in-zircon and zircon saturation temperatures (mostly >750°C) suggest that less water was involved during the partial melting of mantle wedge in this region. Low zircon Eu/Eu* and Ce/Nd ratios (mostly <0.4 and <20, respectively) point towards less oxidized magmatic conditions. We conclude that across-arc geochemical and fluid-flux variations controlled the formation and spatial distribution of Jurassic porphyry deposits in the Gangdese belt.